The integrative use of the strategies of plateau climbing and brainstorming in the achievement of students of the College of Basic Education at the University of Dohuk in the subject of scientific research methods - Nabi, Maolod; Saeed, Diyar; Qasim, Rozan (Humanities Journal of University of Zakho, 2021)
The current research study aims at investigating the effect of the integrative use of both strategies: hill climbing and brainstorming on the achievement of students of Basic College of the University of Duhok in the subject of scientific research methods. The researchers adopted the experimental design with the two equivalent groups with the post-test, an experimental group that was investigated in accordance with the integrative use of the strategies of hill climbing and brainstorming, and another controlled group was studied according to the usual method. Two groups were randomly chosen by the researchers among the third-stage groups in the Department of Education and Psychology at the College of Basic Education. The two groups were distributed in the same manner: that is to say, group B in which there are (32) students represented the experimental group, while group (G) which had 34 students, represented the controlled group. Equivalence between the two groups was achieved in several variables. The researchers prepared an achievement test which included (40) items of MCQs type, and extracted the psychometric characteristics of validity, distinction and stability. After the experiment was conducted, the test was applied, and the statistical data were analyzed using the T-test (t-test) for two independent samples, the results showed that there is a statistically significant difference at the level of (0.05) between the average achievement scores of the experimental and control groups in favor of the experimental group. The researchers reached a general conclusion that the integrated use of the strategies of hill climbing and brainstorming has a crucial effect on the achievement of the participants of the research sample in the subject of scientific research methods. Several recommendations confirmed that it is crucial to utilize the integration in strategies and methods of teaching and put forward some suggestions for future studies.